Grounding of the Longitudinal Distance from the Plow Corps to the Center of the Disk Skimmer - A. R. Normirzayev; A. D. Nuriddinov (Innovations in Science and Technology Vol. 8, 2022)
The article discusses the theoretical grounding of the longitudinal distance from the plow corps to the center of the disk skimmer. Theoretically substantiated the longitudinal distance (I) from the tip of the ploughshare to the center (Od) of the disk and the determination of the distance (y) of the discarding of the soil. The dependence of the longitudinal distance is considered (I) from the angle (\(α\)) of attack, depth (hg) stroke, the radius (r) of the sphere, the radius (R) of the disk and the angle (\(γ\)k) of the ploughshare installation to the furrow wall.